Optical spin-state polarization in a binuclear europium complex towards molecule-based coherent light-spin interfaces - Kuppusamy Senthil Kumar (Nature Portfolio, 2021)
Rare-earth ion (REI)-doped systems are well suited for realising coherent light-spin interfaces, but demonstrations of spectral hole burning (SHB) in optical transitions of REI-based systems have been so far limited to REIs dispersed in matrices. Here, the authors report on transient SHB in a binuclear Eu(III) complex.